Building a Quality Culture in Islamic Educational Institutions - Ramli, Ramli; Bahrani, Bahrani; Ramli, Akhmad (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
Quality culture is a value sistem that creates an atmosphere that supports continuous quality improvement in educational institutions. In this article, quality culture is defined as a combination of values, thoughts, symbols, and practices that influence behavior and beliefs within educational institutions. The process of forming a quality culture involves important elements such as ethics, integrity, teamwork, appreciation, and communication, all of which aim to improve the overall quality of education. Factors that shape a quality culture include the environment, values, role models, routine rituals, and communication networks. Strategies for creating a quality culture include understanding, habituation, and giving rewards and sanctions. Through quality culture-oriented management, the five pillars of educational quality—focus on students, total involvement, measurement, commitment, and continuous improvement—become the foundation for transforming the education sistem. This article also emphasizes the importance of implementing quality culture values ​​in building an education sistem that is ready to face future challenges, based on the principles of fairness, integrity, and continuous learning.